Ultraviolet-curable water-based antifouling resin and preparation method thereof

By using resins containing two carbon hydroxyl groups of polyethylene glycol with polyethylene glycol with bishydroxyl groups in aqueous antifouling UV coatings, combining isocyanate and hydroxyacrylate structures, the antifouling performance in the prior art is solved. and the problem of insufficient environmental protection, efficient anti-fouling and environmentally friendly coating applications have been achieved.

CN119264374APending Publication Date: 2025-01-07ZHEJIANG YOUQIAN SPECIAL MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411390299.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing water-based antifouling UV coatings have shortcomings in antifouling performance and environmental protection, especially because the fluoroalkyl resin used is restricted by the EU's directive forbidden use of C8 fluorocarbons, which leads to its application being restricted.

Method used

Using a polydimethylsiloxane with a bishydroxyl group and a polyethylene glycol structure with two carbon hydroxyl groups, a resin with UV curing ability is formed by reacting with isocyanate, and without an emulsifier. Under water-based acrylate structure combined with a hydroxyl group, it provides photocuring capability.

Benefits of technology

It has achieved solvent-free resin synthesis, has good water-oil contact angle and anti-fouling wiping performance, is widely applicable, can provide anti-fouling ability for a long time, and enhances the formulation adjustment space by emulsifying other resins, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a UV-curable water-based antifouling resin, which comprises the following components by weight: 10-70% of a polysiloxane compound containing two terminal carbon hydroxyl groups, 10-70% of a curing agent, 10-70% of a curing agent, and 10-70% of a solvent. 10%-70% of polyethylene glycol; 5% to 50% of isocyanate containing two isocyanate groups; and 5%-50% of acrylic ester containing one hydroxyl group. The invention also provides a synthesis method for preparing the UV-curable water-based antifouling resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and more particularly to a water-based resin for preparing UV curing coatings and a method for preparing the resin. Background Art

[0002] Traditional solvent-based coatings use organic solvents as diluents, which have poor environmental performance during production and use. Therefore, the development of environmentally friendly coatings has become an inevitable path for the development of global coatings.

[0003] At present, the research on environmentally friendly coatings is mainly focused on water-based coatings. The diluent of water-based coatings is water, which is cheap, easy to obtain, non-toxic and harmless. The coating made from it has low viscosity and good leveling properties. The equipment is easy to clean after coating and there is no residual harmful substances. Therefore, water-based coatings have become the main research direction of environmentally friendly coatings. However, since water-based coatings use water as a diluent, their curing and drying speed is slow and it is not easy to form a flow operation.

[0004] Combining the fast curing speed of traditional solvent-based UV coatings with the environmental protection advantages of water-based coatings, water-based UV-curing coatings have become a major direction of coatings development.

[0005] With the continuous advancement of social science and technology, the popularity of 3C electronic products such as smart phones and tablets in people's lives is increasing, and the market opportunities are growing. Electronic products are used frequently in daily life, and fingers touch electronic products many times a day. The touch of hands will leave human sweat, skin oil, and other pollutants on the surface of electronic products. Consumers have a demand for the surface of electronic products to be beautiful, hygienic, and comfortable. Therefore, in recent years, coating manufacturers have paid more and more attention to the development of antifouling coatings.

[0006] Surface contamination of materials has always existed in people's daily lives. In order to achieve excellent anti-fouling performance, that is, water and oil can easily slide on the surface of the material without leaving traces, anti-fouling resin came into being.

[0007] Antifouling performance can be achieved by reducing the adhesion between pollutants and the coating surface, and the adhesion of pollutants on the coating surface is closely related to the surface energy of the coating surface. When the coating surface energy is lower, the interaction force between pollutants and the coating surface is smaller, and the antifouling performance of the coating surface is stronger. Fluorinated polymers and silicon-containing polymers are research hotspots in the field of low surface energy materials. Fluorinated polymers and silicon-containing polymers can reduce the friction coefficient of the coating surface, increase the surface chemical inertness, and reduce the interaction force between pollutants and the coating surface, thereby achieving an antifouling coating.

[0008] The industry has also conducted some explorations in the field of water-based antifouling UV coatings.

[0009] CN108300274B (prior art 1) discloses a water-based UV-curable anti-fingerprint coating and a preparation method thereof, which uses a fluorine-containing or silicon-containing anti-fouling resin and a water-based UV oligomer as the main body, and through a certain preparation process, a water-based UV-curable anti-fingerprint coating is prepared. However, the anti-fingerprint resin used in this patent contains a lot of organic solvents and needs to be made water-based through other hydrophilic resins, which has certain requirements for other resins, limiting its application scenarios.

[0010] JP2018-104535A (prior art 2) is based on a special polyurethane acrylate aqueous dispersion, providing an aqueous resin composition, a coating agent, and an article having a coating film of the coating agent that can form a coating film with excellent antifouling properties and coating properties. The aqueous resin composition of the invention can form a coating film with antifouling properties, and can be used as a coating agent and adhesive for plastic substrates such as ABS, PC, ABS / PC, PS, PMMA, and PET. However, the antifouling resin used in this technology does not contain low surface energy structures such as silicon and fluorine, and has good antifouling properties for water-based markers, but poor antifouling properties for oil-based pens, which also limits its application scenarios.

[0011] CN110606932A (prior art 3) discloses a photocurable polyurethane acrylate aqueous dispersion and a preparation method thereof, wherein a double-terminal epoxy silicone oil and a single-terminal carboxyl silicone oil are used to react to obtain a hydroxyl-containing modified silicone intermediate A; a caprolactone monomer and a hydroxyl-containing acrylate are reacted to obtain a hydroxyl-containing modified acrylate monomer B; diisocyanate, dimethylol propionic acid and a hydroxyl-containing modified silicone intermediate A are mixed to react to obtain a polyurethane prepolymer grafted with silicone; an inhibitor, an antioxidant and a hydroxyl-containing modified acrylate monomer B are added to the polyurethane prepolymer grafted with silicone to react to obtain a blocked polyurethane acrylate; an organic amine and deionized water are added to the blocked polyurethane acrylate to react to obtain a photocurable polyurethane acrylate aqueous dispersion. After forming a paint film, the product has strong anti-fouling and anti-graffiti properties, is durable, and has good elastic feel and anti-adhesion properties. However, the modified silicone oil used in this patent has a large molecular weight, poor solubility in other organic resins, low hardness, and poor anti-fouling durability, which limits its application scenarios.

[0012] CN111171702A (prior art 4) discloses a dual-cured polyurethane aqueous dispersion and water-based UV coating. The dual-cured polyurethane aqueous dispersion includes: a first dispersion, a UV-curable carboxylic acid-type aqueous polyurethane dispersion; a second dispersion, a non-ionic aqueous polyurethane dispersion containing carbodiimide groups. The second dispersion uses dual-end bishydroxyalkyl silicone oil / single-end bishydroxyalkyl silicone oil to improve boiling water resistance and significantly reduce the friction coefficient. However, due to the high viscosity of the raw materials involved in this technology, solvents must still be used during synthesis; and the carbodiimide structure in the molecule has a high viscosity and poor stain resistance.

[0013] CN107286319A (prior art 5) discloses an organic fluorine-modified water-based UV curing resin, which is prepared by starting with a trifunctional or tetrafunctional polyol as a starting material, reacting with a diisocyanate by addition polymerization, introducing a hydrophilic group through a diol with a carboxyl group, and introducing an acrylic acid double bond and organic fluorine modification by end-capping with hydroxy acrylate and perfluorooctanol. The water-based UV curing resin has a high double bond density and low surface tension, as well as a low molecular weight and good water solubility, and can be used to prepare a coating with leveling fluidity and high gloss, and has a wide range of applications.

[0014] CN103333285B (prior art 6) uses easily available fluorinated acrylate monomers, fluorine-free acrylic monomers, and chain transfer diols as raw materials, and obtains fluorinated alkyl diols by free radical polymerization, and then polymerizes the side chain fluorinated alkyl diol monomers to the waterborne polyurethane hard segment. At the same time, a photosensitive reactive group is introduced at the end of the polyurethane chain to prepare a UV-curable side chain fluorinated waterborne polyurethane resin, and then blended with an auxiliary agent to obtain a UV-curable waterborne coating. The coating prepared by this technology has both water-based environmental protection and UV fast curing characteristics, and has excellent solvent resistance, weather resistance, high gloss, anti-fouling and self-cleaning properties, and can be used for waterproof and anti-corrosion coatings for building exterior walls, automobiles, ships, etc.

[0015] CN103992460B (prior art 7) provides a polyurethane acrylate oligomer, which has a high hydrophilic angle by introducing silicon and fluorine into the interior of the polyurethane acrylate oligomer; and has high anti-fouling performance by utilizing the high hydrophilicity provided by the ethoxy group in polyethylene glycol. After the coating made of the polyurethane acrylate oligomer is cured by ultraviolet light, the hydrophilic angle of the paint film is as high as 100-120°, and it has excellent stain resistance. The oil pen stains can be wiped off without leaving any traces.

[0016] CN103980215B (prior art 8) provides a waterborne polyurethane acrylic oligomer, which contains an ethoxy group and a fluorine-containing group. The ethoxy group makes the paint film obtained by curing the waterborne UV-curable coating have good water dispersibility, and the fluorine-containing group makes the paint film obtained by curing the waterborne UV-curable coating have excellent stain resistance and anti-graffiti properties, and the anti-fouling effect can be achieved without the need for adding an external anti-fouling additive.

[0017] CN110121515A (prior art 9) provides a fluorine-containing active energy ray-curable resin, a composition containing the fluorine-containing active energy ray-curable resin and a cured coating film of the composition, wherein the fluorine-containing active energy ray-curable resin is characterized in that it has: a polymer structure of a free radical polymerizable unsaturated monomer, a poly (perfluoroalkylene ether) chain, a free radical polymerizable unsaturated group and a neutralized salt structure of an acid group.

[0018] The above prior arts (prior arts 5-9) use fluoroalkyl resins (structures such as perfluorooctyl and dodecafluoroheptyl) to provide stain resistance. However, with the implementation of the EU directive prohibiting the use of C8 fluorocarbon compounds, more and more studies have shown that perfluorocarbon compounds (PFCs) are harmful and potentially carcinogenic to organisms, and the application areas of fluoroalkyl fluorinated acrylates will be limited.

[0019] Therefore, the industry needs to develop new water-based antifouling resins to meet environmental protection needs. Summary of the invention

[0020] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides a UV-curable water-based antifouling resin, the components of which include, by weight:

[0021]

[0022] The resin of the present invention provides antifouling properties through a polydimethylsiloxane containing two carbon hydroxyl groups; its structure is as follows

[0023]

[0024] or

[0025]

[0026] The molecular weight range is 500-5000.

[0027] Polydimethylsiloxane containing two carbon hydroxyl groups has similar chemical properties to other diols and can participate in the reaction with isocyanate to obtain the chemical structure we want.

[0028] Preferably, the UV-curable water-based antifouling resin of the present invention comprises, by weight:

[0029]

[0030] The resin of the present invention uses a dihydroxy polyethylene glycol structure as a non-ionic hydrophilic group to make the resin water-based without the assistance of an external emulsifier or a hydrophilic solvent; the molecular weight of the polyethylene glycol is in the range of 300 to 5000.

[0031] The resin of the present invention provides light curing capability through an acrylate structure containing a hydroxyl group. One or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, pentaerythritol triacrylate, trimethylolpropane diacrylate and pentaerythritol trimethacrylate can be selected.

[0032] The resin is connected to the resin by an isocyanate containing two isocyanate groups, and the hydrophilic group / polydimethylsiloxane / photocuring group is connected to the resin. One or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), phenylene diisocyanate (PDI), hexamethylene-1,6-diisocyanate (HDI), isophorone diisocyanate (IPDI), cyclohexane diisocyanate (HPDI), methylcyclohexyl diisocyanate (HTDI), perhydrodiphenylmethane diisocyanate (HMDI), xylylene diisocyanate (XDI), perhydroxylylene diisocyanate (HXDI), tetramethylxylylene diisocyanate (TMXDI) and dimer acid diisocyanate (DDI) can be selected.

[0033] The toluene diisocyanate may be 2,4-toluene diisocyanate or 2,6-toluene diisocyanate.

[0034] The diphenylmethane diisocyanate is diphenylmethane-4,4'-diisocyanate or diphenylmethane-2,4'-diisocyanate.

[0035] The perhydrodiphenylmethane diisocyanate is perhydrodiphenylmethane-2,4'-diisocyanate or perhydrodiphenylmethane-4,4'-diisocyanate.

[0036] The present invention also provides a method for synthesizing the UV-curable water-based antifouling resin:

[0037] In a glass flask equipped with a stirring device, a thermometer, a condenser and a dropping device, a polysiloxane compound containing carbon hydroxy groups at both ends, polyethylene glycol, an isocyanate containing two isocyanate groups, and bismuth isooctanoate are added, stirring is started under an air flow, and the temperature is raised to 80°C, and the reaction is carried out until the isocyanate (-NCO) equivalent reaches 1200-1400 g / mol, an acrylate containing one hydroxyl group is added, the temperature is raised to 80°C, and the reaction is carried out until the isocyanate (-NCO) equivalent reaches 42000-50000 g / mol, and the disappearance of the isocyanate group is confirmed by IR spectroscopy to obtain a UV-curable water-based antifouling resin.

[0038] The resin of the present invention has the following advantages:

[0039] 1) The resin of the present invention has a hydrophilic structure, does not contain an external emulsifier, and the dispersion is stable during thermal storage. The resin itself can be emulsified in water, and the particle size is less than 80nm; and the resin of the present invention has a certain ability to emulsify other resins.

[0040] 2) The resin of the present invention has an anti-fouling structure, good water-oil contact angle and anti-fouling wiping performance.

[0041] 3) The resin of the present invention has good compatibility with a variety of UV resins / monomers and has wide applicability; at the same time, it is helpful for the emulsification of other UV resins and monomers, thereby increasing the adjustment space of the formula.

[0042] 4) The resin of the present invention can be UV cured to produce long-lasting antifouling ability, and the number of times the marker pen is repeatedly applied and wiped is high.

[0043] 5) The synthesis process of the resin of the present invention focuses on atom economy and does not use solvents; it does not use biologically enriched raw materials such as organic tin and long carbon chain organic fluorides, which is more green and environmentally friendly. DETAILED DESCRIPTION

[0044] Example 1

[0045] 1. Preparation of water-based antifouling resin

[0046] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 100 g of Shin-Etsu Chemical KF-6000 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 1000 g / mol), 100 g of polyethylene glycol 1000 (molecular weight of 1000 g / mol), 66.7 g of isophorone diisocyanate, and 0.14 g of bismuth isooctanoate (catalyst) were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 1200 to 1400 g / mol, 59.6 g of pentaerythritol triacrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 1 was obtained.

[0047] 2. Preparation of water-based antifouling resin dispersion

[0048] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 105 g of the water-based antifouling resin of Example 1 and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 1 is obtained.

[0049] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 1, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 1 is obtained.

[0050] Example 2

[0051] 1. Preparation of water-based antifouling resin

[0052] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 200g of Shin-Etsu Chemical KF-6001 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 2000g / mol), 200g of polyethylene glycol 2000 (molecular weight of 2000g / mol), 66.7g of isophorone diisocyanate, and 0.23g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80°C, and the reaction was carried out until the isocyanate (-NCO) equivalent reached 2100-2300g / mol, 59.6g of pentaerythritol triacrylate was added, the temperature was raised to 80°C, and the reaction was carried out until the isocyanate (-NCO) equivalent reached 42000-50000g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 2 was obtained.

[0053] 2. Preparation of water-based antifouling resin dispersion

[0054] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 105 g of the water-based antifouling resin of Example 2 and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 2 is obtained.

[0055] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 1, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 2 is obtained.

[0056] Example 3

[0057] 1. Preparation of water-based antifouling resin

[0058] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 100 g of Shin-Etsu Chemical KF-6000 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 1000 g / mol), 200 g of polyethylene glycol 2000 (molecular weight of 2000 g / mol), 66.7 g of isophorone diisocyanate, and 0.18 g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 1700 to 1900 g / mol, 59.6 g of pentaerythritol triacrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 3 was obtained.

[0059] 2. Preparation of water-based antifouling resin dispersion

[0060] 105 g of the water-based antifouling resin of Example 3 and 245 g of deionized water were added to a 1-liter sealable glass container equipped with a stirrer and a heater. The mixture was heated at 60° C. for 180 minutes while stirring at 300 rpm. The mixture was then cooled to room temperature while stirring and filtered with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 3 was obtained.

[0061] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 3, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 3 is obtained.

[0062] Example 4

[0063] 1. Preparation of water-based antifouling resin

[0064] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 100 g of Shin-Etsu Chemical KF-6000 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 1000 g / mol), 100 g of polyethylene glycol 1000 (molecular weight of 2000 g / mol), 66.7 g of isophorone diisocyanate, and 0.13 g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 1200 to 1400 g / mol, 115.2 g of dipentaerythritol pentaacrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 4 was obtained.

[0065] 2. Preparation of water-based antifouling resin dispersion

[0066] 105 g of the water-based antifouling resin of Example 4 and 245 g of deionized water were added to a 1-liter sealable glass container equipped with a stirrer and a heater. The mixture was heated at 60° C. for 180 minutes while stirring at 300 rpm. The mixture was then cooled to room temperature while stirring and filtered with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 4 was obtained.

[0067] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 4, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 4 is obtained.

[0068] Example 5

[0069] 1. Preparation of water-based antifouling resin

[0070] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 200 g of Shin-Etsu Chemical KF-6001 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 2000 g / mol), 100 g of polyethylene glycol 1000 (molecular weight of 1000 g / mol), 66.7 g of isophorone diisocyanate, and 0.18 g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 1700 to 1900 g / mol, 59.6 g of pentaerythritol triacrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 5 was obtained.

[0071] 2. Preparation of water-based antifouling resin dispersion

[0072] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 105 g of the water-based antifouling resin of Example 5 and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 5 is obtained.

[0073] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 5, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 5 is obtained.

[0074] Example 6

[0075] 1. Preparation of water-based antifouling resin

[0076] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 100 g of Shin-Etsu Chemical KF-6000 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 1000 g / mol), 50 g of polyethylene glycol 500 (molecular weight of 1000 g / mol), 66.7 g of isophorone diisocyanate, and 0.11 g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 1100 to 1200 g / mol, 59.6 g of pentaerythritol triacrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 6 was obtained.

[0077] 2. Preparation of water-based antifouling resin dispersion

[0078] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 105 g of the water-based antifouling resin of Example 6 and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 6 is obtained.

[0079] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 6, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 6 is obtained.

[0080] Example 7

[0081] 1. Preparation of water-based antifouling resin

[0082] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 300 g of Shin-Etsu Chemical KF-6002 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 3000 g / mol), 300 g of polyethylene glycol 3000 (molecular weight of 1000 g / mol), 66.7 g of isophorone diisocyanate, and 0.34 g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 3500 to 3700 g / mol, 59.6 g of pentaerythritol triacrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 7 was obtained.

[0083] 2. Preparation of water-based antifouling resin dispersion

[0084] 105 g of the water-based antifouling resin of Example 7 and 245 g of deionized water were added to a 1-liter sealable glass container equipped with a stirrer and a heater. The mixture was heated at 60° C. for 180 minutes while stirring at 300 rpm. The mixture was then cooled to room temperature while stirring and filtered with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 7 was obtained.

[0085] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 7, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 7 is obtained.

[0086] Example 8

[0087] 1. Preparation of water-based antifouling resin

[0088] In a glass flask equipped with a stirring device, a thermometer, a condenser, and a dropping device, 100 g of Shin-Etsu Chemical KF-6000 (a polysiloxane compound containing carbon hydroxyl groups at both ends, with a molecular weight of 1000 g / mol), 100 g of polyethylene glycol 1000 (molecular weight of 2000 g / mol), 66.7 g of isophorone diisocyanate, and 0.13 g of bismuth isooctanoate were added, stirring was started under air flow, and the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 1200 to 1400 g / mol, 23.2 g of hydroxyethyl acrylate was added, the temperature was raised to 80° C., and the reaction was performed until the isocyanate (-NCO) equivalent reached 42000 to 50000 g / mol, and the disappearance of the isocyanate group was confirmed by IR spectroscopy. The water-based antifouling resin of Example 8 was obtained.

[0089] 2. Preparation of water-based antifouling resin dispersion

[0090] 105 g of the water-based antifouling resin of Example 8 and 245 g of deionized water were added to a 1-liter sealable glass container equipped with a stirrer and a heater. The mixture was heated at 60° C. for 180 minutes while stirring at 300 rpm. The mixture was then cooled to room temperature while stirring and filtered with a 300-mesh stainless steel filter under slight pressure. Resin dispersion A of Example 8 was obtained.

[0091] In a 1-liter sealable glass container equipped with a stirrer and a heater, add 70 g of the water-based antifouling resin of Example 8, 35 g of dipentaerythritol hexaacrylate, and 245 g of deionized water. Stir at 300 rpm while heating the system, and heat and stir at 60°C for 180 minutes. Then, cool to room temperature while stirring, and filter with a 300-mesh stainless steel filter under slight pressure. Resin dispersion B of Example 8 is obtained.

[0092] The testing and evaluation of various property values ​​of the resin according to the embodiment of the present invention are performed as follows.

[0093] [Dispersion particle size]

[0094] The particle size of the resin dispersion is closely related to the hydrophilicity of the aqueous resin / resin composition and has an impact on the storage properties of the dispersion. The particle size of the aqueous dispersion is measured by a dynamic light scattering device (reference Malvern Particle Analyzer Processor model 7027 / 4600SM). It is expressed in nm.

[0095] [Dispersion storage performance]

[0096] The obtained resin dispersion was placed in an oven at 60°C for 7 days and its appearance was observed. If separation or gelation occurred, it was judged as NG.

[0097] [Coating transparency]

[0098] The transparency of the coating after curing is closely related to the application scenario. When the coating cannot achieve transparency, it is usually a paint film defect, often accompanied by problems such as fogging, coloring, mottled, orange peel, and shrinkage.

[0099] The tested resin dispersion was mixed with a 5% aqueous solution of BASF Irgacure at a ratio of 100:20, coated on a glass substrate, baked at 60°C for 10 minutes to drain the water, and cured by ultraviolet light. The ultraviolet light energy was 600mW / cm 2 , the dry film thickness is 25μm. After curing, observe the transparency of the paint film.

[0100] [Coating antifouling performance]

[0101] The tested resin dispersion was mixed with a 5% aqueous solution of BASF Irgacure at a ratio of 100:20, coated on a polycarbonate substrate, baked at 60°C for 10 minutes to drain the water, and cured by ultraviolet light. The ultraviolet light energy was 600mW / cm 2 , dry film thickness is 25μm.

[0102] The hardness, water / oil contact angle, and anti-fouling times of the coating can be tested according to the corresponding test standards to evaluate the anti-fouling performance.

[0103] 1. Coating hardness:

[0104] The tested resin dispersion was mixed with a 5% aqueous solution of BASF Irgacure at a ratio of 100:20, coated on a polycarbonate substrate, baked at 60°C for 10 minutes to drain the water, and cured by ultraviolet light. The ultraviolet light energy was 600mW / cm 2 , dry film thickness is 25μm.

[0105] The hardness test is carried out by using a special metal stand fixed at a right angle, applying uniform pressure, and scratching the cured coating with the tip of a sharp pencil. After the test, pencils of different hardness are replaced. The test results are reported as the pencil hardness above which the coating is obviously damaged.

[0106] The pencil hardness scale from soft to hard is: 9B–8B–7B–6B–5B–4B–3B–2B–1B–HB–F–1H–2H–3H–4H–5H–6H–7H–8H–9H. High coating hardness is desirable to provide resistance to coating damage.

[0107] 2. Water / oleic acid contact angle:

[0108] According to GB / T23764-2009 standard, the water / oleic acid contact angle of the coating is tested by a contact angle tester. The larger the contact angle, the better the antifouling property.

[0109] 3. Number of times the coating resists contamination:

[0110] Apply a zebra blue oil pen on the coating, let it stand for 1 minute, then wipe it with Asahi Kasei nonwoven fabric (BEMCOT), and record the number of times when it cannot be wiped off.

[0111] Table 1. Test data, surface properties after film formation and antifouling properties of resin dispersion A

[0112]

[0113] It can be seen from the test results that the resin dispersion coating made of the water-based antifouling resin according to the embodiment of the present invention has good antifouling ability after curing.

[0114] Table 2. Test data of resin dispersion B and appearance after film formation

[0115]

[0116] In the preparation composition of the dispersion B of each embodiment, in addition to the water-based antifouling resin according to the present invention, there are other resins. It can be seen from the test in Table 2 that the water-based antifouling resin of the present invention can be emulsified in water and also has a certain ability to emulsify other resins.

[0117] Although embodiments of the present invention are described herein, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A UV-curable water-based antifouling resin, comprising, by weight:

2. The UV-curable water-based antifouling resin according to claim 1, wherein: The polysiloxane compound containing two terminal carbon hydroxyl groups is polydimethylsiloxane, and its structure is as follows: or The molecular weight range is 500-5000.

3. The UV-curable water-based antifouling resin according to claim 1, wherein: The components by weight include: 15% to 50% of a polysiloxane compound containing carbon hydroxyl groups at both ends; Polyethylene glycol 15% to 50%; Isocyanates containing two isocyanate groups 10% to 30%; Acrylate containing one hydroxyl group 10% to 30%.

4. The UV-curable water-based antifouling resin according to claim 1, wherein: The acrylic acid ester containing one hydroxyl group may be selected from one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, pentaerythritol triacrylate, trimethylolpropane diacrylate and pentaerythritol trimethacrylate.

5. The UV-curable water-based antifouling resin according to claim 1, wherein: The isocyanate containing two isocyanate groups can be selected from one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), benzene diisocyanate (PDI), hexamethylene-1,6-diisocyanate (HDI), isophorone diisocyanate (IPDI), cyclohexane diisocyanate (HPDI), methylcyclohexyl diisocyanate (HTDI), perhydrodiphenylmethane diisocyanate (HMDI), xylylene diisocyanate (XDI), perhydroxylylene diisocyanate (HXDI), tetramethylxylylene diisocyanate (TMXDI) and dimer acid diisocyanate (DDI).

6. The UV-curable water-based antifouling resin according to claim 5, wherein: The toluene diisocyanate may be 2,4-toluene diisocyanate or 2,6-toluene diisocyanate.

7. The UV-curable water-based antifouling resin according to claim 5, wherein: The diphenylmethane diisocyanate is diphenylmethane-4,4'-diisocyanate or diphenylmethane-2,4'-diisocyanate.

8. The UV-curable water-based antifouling resin according to claim 5, wherein: The perhydrodiphenylmethane diisocyanate is perhydrodiphenylmethane-2,4'-diisocyanate or perhydrodiphenylmethane-4,4'-diisocyanate.

9. A method for preparing the UV-curable water-based antifouling resin according to claim 1, comprising the following steps: In a glass flask equipped with a stirring device, a thermometer, a condenser and a dropping device, a polysiloxane compound containing carbon hydroxy groups at both ends, polyethylene glycol, an isocyanate containing two isocyanate groups, and bismuth isooctanoate are added, stirring is started under an air flow, and the temperature is raised to 80°C, and the reaction is carried out until the isocyanate (-NCO) equivalent reaches 1200-1400 g / mol, an acrylate containing one hydroxyl group is added, the temperature is raised to 80°C, and the reaction is carried out until the isocyanate (-NCO) equivalent reaches 42000-50000 g / mol, and the disappearance of the isocyanate group is confirmed by IR spectroscopy to obtain a UV-curable water-based antifouling resin.

Citation Information

Patent Citations

  • A UV-curable side-chain fluorinated waterborne polyurethane coating and its preparation method

    CN103333285B

  • A waterborne polyurethane acrylate oligomer, its preparation method, and a waterborne UV-curable coating.

    CN103980215B

  • Polyurethane acrylate oligomers, their preparation methods, and coatings prepared therefrom

    CN103992460B

  • Organo-fluorine modified waterborne UV curing resin and preparation method thereof

    CN107286319A

  • A water-based UV-curable anti-fingerprint coating and its preparation method

    CN108300274B